Designing Arabic Language Learning Materials with Augmented Reality: A 3D Assemblerword-Based Media Innovation - Paputungan, Moh. Zulkifli; Arif, Muh.; Sarif, Suharia (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2025)
Arabic language learning at MIN 1 Gorontalo still relies heavily on conventional methods, which result in low student motivation and limited engagement. This study aims to explore the integration of Augmented Reality (AR) technology in developing Arabic teaching materials using 3D Assemblerword-based media. By leveraging AR technology, the learning process is expected to become more interactive and engaging. The research employed a Research and Development (R&D) approach using the ADDIE model. The study involved fifth-grade students from MIN 1 Gorontalo Regency, with two groups comprising a total of 60 students. The findings indicate that AR-based media significantly improved students’ understanding of Arabic materials and increased their learning motivation. This study contributes to the advancement of innovative and effective instructional strategies in Arabic language education.